Reoperations in the primary hyperparathyroidism - Morelli, Raúl; Barreiro, Claudia; Castro, Teresa; Bounous, Mario (Cirugía del Uruguay, 1996)
Surgery of primary hyperparathyroidism is ocasional in our country. By means of three reinterventions for persistence in a total of 19 patients operated on primary hyperparathyroidism, a study on the matter is rea/ized. Causes of reintervention are analyzed, being the most importan/ mu/tiple patho/ogica/ g!ands and surgeon's inexperience. As a localization test, tecnecio 99m sestamibi have better certainty. We insist on lateral boarding of neck when the gland is /oca/ized.